Cubic Spherical Neutrosophic Numbers for Communication Effectiveness Evaluation of Intangible Cultural Heritage Traditional Music - Fanfu Lu (Neutrosophic Sets and Systems)
To protect cultural identity and encourage intergenerational continuity, it is essential to preserve and share intangible cultural heritage (ICH), especially traditional music. As digital media and communication technology have advanced, it is now crucial to assess how well different platforms communicate classical music. To evaluate traditional music's communication efficacy as a component of ICH, this study suggests an assessment approach. Reach of the audience, cultural authenticity, multimedia use, information transmission across generations, public awareness, and emotional resonance are important factors. Eight sample communication techniques are evaluated, ranging from instructional seminars and live performances to virtual reality and mobile applications. To determine which approaches best strike a compromise between cultural preservation and contemporary participation, the study uses a hybrid qualitative-quantitative methodology. This study uses Cubic Spherical Neutrosophic Numbers to evaluate the criteria and alternatives and overcome vague information. The results demonstrate how digital resources may be used to supplement traditional techniques, increasing traditional music's sustainability and exposure in modern culture.